PS 04-25 ASSOCIATION OF TCF7L2 AND PPARγ GENE VARIANTS WITH TYPE 2 DIABETES MELLITUS IN NORTH INDIAN POPULATION. (September 2016) - Verma, Sushma; Srivastava, Neena; Banerjee, Monisha
Abstract : Objective: To determine the association of biochemical parameters and genetic polymorphisms in Transcription factors 7 like 2 ( TCF7L2 ) and peroxisome proliferator-activated receptor-γ ( PPARγ ) genes with Type 2 Diabetes Mellitus (T2DM) in north Indians. Design and Method: Subjects (n = 442) from North India were subjected to anthropometric, biochemical tests and genotyped for 4 different SNPs in TCF7L2 and PPARγ genes. Specific primers and restriction enzymes were used for polymerase chain reaction (PCR) and restriction fragment length polymorphism (PCR-RFLP) respectively. Statistical analyses were done by SPSS (v. 21.0) and SHEsis (v. online). Results: Blood glucose, cholesterol, blood pressure systolic, blood pressure diastolic, low density lipoprotein, serum creatinine were significantly increased while High-density lipoprotein and Very low density lipoprotein showed significant decrease in T2DM cases when compared to controls (P < 0.005). The frequency of 'TT' genotype of TCF7L2 rs7903146 (C/T) polymorphism was significantly lower in cases as compared to controls (P < 0.004, OR 0.34). 'T' allele of TCF7L2 rs7903146 (C/T) prevalence was significantly lower in cases as compared to controls (P < 0.03, OR 0.78). Individuals with 'AG' genotype of PPARγ gene rs11128600 (A/G) showed 1.13 times higher risk. PPARγ SNP rs17036314 (C/G) was monomorphic and TCF7L2 rs12255372 (G/T) did not show association in our population. The individuals with genotypic combinations with GG/CC (+/-, +/+) and GG/CT (+/-, +/+) of TCF7L2 SNPs showed slightly higher risk of T2DM whereas TG/TT (-/+) genotype frequency was significantly higher in controls. Conclusions: Our results suggested that TCF7L2 gene polymorphisms showed significant association with type 2 diabetes and the 'T' allele of rs7903146 (C/T) in TCF7L2 gene showed a protective role against T2DM in the study population.